Histopathological Examination to Evaluate the Cytotoxicity of Polyhydroxybutyrate Nano-Particles (PHB-NPs) in Mice Livers - Jenan Atiyah Ghafil; May Talib Flayyih (World Journal of Experimental Biosciences, 2021)
Polyhydroxybutyrate (PHB) is considered a promising material in various medical, industrial, and food fields. The use of any substance in these areas must pass toxicity tests in vivo and in vitro. The current study aims to estimate the cytotoxicity of PHB nanoparticles (PHB-NPs) in vivo by checking the effect of PHB-NPs and other forms of this chemical on liver tissue. In this study, PHB-NPs were produced in the laboratory by exposing PHB to ultrasound waves in gradient pH. The formation of PHB-NPs was estimated using a scanning electron microscope (SEM). Four groups of mice were injected intraperitoneally with a treatment dose of PHB, PHB-NPs, PHB-cefotaxime (CTX), and CTX. The control group was the mice injected intraperitoneally with normal saline. The mice were dissected and liver slides of mice groups were prepared for histopathological examination. The results showed the efficiency of the method used in preparing the PHB-NP. The results of the experiments also showed that there was no change in the liver tissue of the mice of the four groups when compared with the liver tissue of the control group. The present study concluded that there is no toxicity or any other effect of administrating the mice with a treating dose of PHB, PHB-NP, PHB-NP+CTX, and CTX on the histologic features of the experimental animals. This study proves the safety of PHB-NPs and combines materials for use in in vivo study but after further cytotoxic experiments.
Keywords: Histopathological study, Liver, Mouse, Polyhydroxybutyrate Nano-Particles.